OPTIMAL CAPITAL STRUCTURE ANALYSIS OF PT TRIPUTR AGRO PERSADA TBK - Samuel Aquila, Michael
PT Triputra Agro Persada Tbk is a Crude Palm Oil (CPO) company that has operated in Indonesia since 2005. This company operates in Jambi, Central Kalimantan, and East Kalimantan. Since its inception, PT Triputra Agro Persada Tbk has continued to support CPO production in Indonesia. The company believes that the CPO industry in Indonesia has enormous potential in the future. The company can take advantage of this potential to make profits through CPO production. Therefore, the company continues to evaluate its production capacity. In 2023, PT Triputra Agro Persada Tbk will increase production capacity with an expansion plan that will cost IDR 900 billion.